GALNT6 associated with O-GlcNAcylation contributes to the tumorigenesis of oral squamous cell carcinoma - Junfeng Yan; Xuan Tang; Yingying Zhou; Xin Xiong (Discover Oncology)
Abstract Background We aimed to explore the regulatory gene associated with O-GlcNAcylation in oral squamous cell carcinoma (OSCC) and the underlying mechanism. Methods The publicly available gene expression datasets (GSE23558 and GSE25099) were downloaded from Gene Expression Omnibus database. Differentially expressed genes (DEGs) between tumor and controls were identified by limma package. O-GlcNAcylation related genes with differential expression were screened and filtered by LASSO, RF and SVM machine learning models. The expression of one key gene (GALNT6) was validated in OSCC cells by qRT-PCR assay. Immunohistochemistry staining was used to detect the expression of GALNT6 in clinical tissue samples. GALNT6 expression was knocked down by siRNA transfection. CCK8, cell clone, cell scratch assays and transwell assay were employed to examine the proliferation, migration and invasion ability of OSCC cells. Results Total 16 O-GlcNAcylation-related genes were found to be differentially expressed in OSCC, which were significantly enriched in glycosylation. Four key genes (MUC15, ADAMTS12, GALNT6 and FUT6) were identified with promising prognostic value by three machine learning algorithms. GALNT6 were aberrantly upregulated in OSCC cells and tissues. After GALNT6 knockdown, the cell viability, colony formation, and wound healing ability were obviously reduced, in parallel with suppressed metastasis ability in OSCC cells. Conclusion GALNT6 associated with O-GlcNAcylation is overexpressed in OSCC and its knockdown inhibits the growth of OSCC in vitro.